THE IMPORTANCE OF PRE-TRIAL CHAMBER IN CRIMINAL PROCEEDINGS. PROCEDURE AND CONTROVERSIAL ISSUES - Mirel Georgian PETRE (Challenges of the Knowledge Society, 2022)
Following a legislative proposal to eliminate the pre-trial chamber phase from the criminal proceedings, I decided to study its properties and express my opinion on its importance. Analyzing the pre-trial chamber and the trial procedure, I found that its delimitation from the trial phase by clear differences imposed by the code of criminal procedure is of particular importance. Its nature is to carry out a complex legal control over the criminal investigation phase in order to give effectiveness to the fundamental principles of the criminal proceedings and to guarantee compliance with the legal provisions in force. Through my study, I aim to delimit some notions that have a practical, but also theoretical importance, in order to identify and distinguish the procedures regulated in the new code of criminal procedure regarding the institution of the pre-trial chamber. I intend to set out the procedure, but also the issues discussed in contradiction in the specialized practice, as well as in doctrine, in a technical manner in order to outline its essential features and to delimit the usual procedure from other derived procedures in which the legislator used the phrase ”pre-trial chamber judge”, although this is not found in the pre-trial chamber phase. Also, the delimitation of these proceedings leads to a practical understanding of the functionality of the pre-trial chamber and to the elimination of the confusions of judicial proceedings conducted in a particular procedure.